Shipping Cost Optimization Using Least Cost and Stepping Stone Method at The Xender Brand Sandal Factory - I Nugraha; YC Winursito; T P Sari (BIOMEJ, 2023)
. The optimization model is one of the system analysis models identified with operation research. The transportation model determines the lowest cost for sending one item from several sources to several destinations as a collection of interconnected elements forming a single unit to integrate data, process, and store. Goods delivery transportation services are the use of software to provide services in the form of delivery of goods that are interrelated and structured to achieve a specific goal. The working principle of the Least cost method is to prioritize allocations with the most negligible unit cost (most minor cost per unit). This research was carried out using the Least Cost method so that companies can determine the optimal cost of shipping goods.